The spread of christianity in Yorubaland of Nigeria: an historical perspective - Thani, Taofeek Muhammed (International Institute of Islamic Thought and Civilization, International Islamic University Malaysia, 2012)
This study is both historical and analytical and examines the recent development of missionary activities and its impact on the Muslims in Yorubaland. It traces the origin of Christianity in Nigeria and identifies some salient factors that may have triggered the spread of Christian influence in Yorubaland and highlights the roles played by mainstream churches to complement the efforts of missionary activities: it shows that churches, schools, health centers and chapels were built around towns and cities to further facilitate the process of evangelization. The findings show that Christianity has become more integrated into the Nigerian society and has impacted greatly on the local culture. This is facilitated by the introduction of a new way of life which includes western education, the romanization of the Yoruba language, modes of dressing and the use of the English language as the medium of communication among other changes. All these would not have been possible had it not been for the collaborative efforts between the missionaries and the colonial masters. Data for this study are drawn from both primary and secondary sources in forms of books, reports, scholarly journals, magazines, and occasional papers, proceedings of relevant conferences, newspapers and internet sources. Interviews were conducted to complement the qualitative methodology upon which this research is grounded. The research concludes, in view of the findings, by suggesting a constructive resolution of religious disputes and dialogue as a means of establishing a long-lasting peaceful co-existence between Muslims and Christians in the South Western Nigeria.